"The vital importance of the communicative identity concept in different languages" - ZAXIDOVA GULNOZA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This is an analysis of the main trends in the study of linguistic personality in contemporary linguistics. There has long been a tendency in linguistics to study language personality in depth: its model, the projection of an interdisciplinary term into the field of linguistics, priorities reflected in vocabulary, behavioral reactions, vocabulary, ethnosemantics, and much more. One of the topical areas of research is the understanding of the human phenomenon through natural languages".